Islamic banking in Nigeria : issues and prospects / Nuruddeen Abba Abdullahi. - Abdullahi, Nuruddeen Abba (Universiti Teknologi Mara Selangor, 2016)
The Nigerian banking reform precipitated the adoption of Islamic banking and finance in 2009 as additional door to banking mechanism in the country. However, the implementation of the Islamic banking or non-interest banking has generated a lot of debate, specifically because its foundations are based on Islamic religion. This paper briefly reviews the concept, the challenges and prospects of Islamic banking in Nigeria. The paper relies on the secondary sources by reviewing and analysing various works on the subject. A reflection on the size of its population and the developmental opportunities indicates that Nigeria has the prospect of becoming the hub centre of Islamic finance in Africa. Yet there are numerous challenges to the development of the Islamic banking system in the country, including misrepresentation of the system, lack of linkages and investment institutions, lack of adequate knowledge, as well as shroud business ethos and corruption, which is endemic in the country. The paper recommends the need for greater public awareness about Islamic banking and creation of enabling environment (i.e. the legal, accounting and taxation systems) for the working of Islamic financial system.